Undiagnosed Ocular Syphilis Treated With Immunosuppressive Therapy. (July 2019) - Patel, Palak R.; Pittner, Andrew C.; Merrill, Pauline T.
Purpose: The purpose of this case series is to illustrate the importance of diagnosis and treatment of infectious uveitis and to suggest syphilis screening guidelines before the initiation of immunosuppressive therapy. Method: A retrospective case series (2016-2018) from a Chicago-area academic retina practice was conducted. Primary outcomes include ocular syphilis response to discontinuation of immunomodulatory agents and initiation of penicillin treatment as assessed by improvement of visual acuity and ocular inflammation. Results: Three patients with ocular syphilis in the setting of immunosuppressive therapy are presented. Two cases were identified of misdiagnosed ocular syphilis in patients initially treated with immunosuppressive therapy including adalimumab for their uveitis. A third case of ocular syphilis in a patient being treated with infliximab for ankylosing spondylitis is also presented. Once laboratory testing confirmed the presence of syphilis, immunosuppressive therapies were immediately stopped; signs of inflammation and visual acuity improved with adequate treatment for neurosyphilis including intravenous penicillin. Conclusions: Ocular syphilis may present in a variety of ways and cannot be ruled out without appropriate testing. Syphilitic uveitis should be on the differential of any patient presenting with ocular inflammation and screened for accordingly. It is particularly critical that syphilis be screened for before starting immunosuppressive treatment for uveitis to minimize the risk of long-term ocular damage from a treatable infectious uveitis. These cases convey the importance of establishing guidelines around screening for syphilis prior to starting immunosuppressive treatment for uveitis.